Analysis of new psychoactive substances in oral fluids by means of microextraction by packed sorbent followed by ultra‐high‐performance liquid chromatography–tandem mass spectrometry. Issue 5 (27th November 2017) - Rocchi, Rachele; Simeoni, Maria Chiara; Montesano, Camilla; Vannutelli, Gabriele; Curini, Roberta; Sergi, Manuel; Compagnone, Dario
Abstract: In recent years, new drugs, commonly known as new psychoactive substances (NPS), appeared on the market, which include, among others, synthetic cannabinoids, cathinones, and tryptamine analogs of psilocin. The aim of this work was to develop and validate a new method for simultaneous screening and quantification of 31 NPS in oral fluid by ultra‐high‐performance liquid chromatography‐tandem mass spectrometry (UHPLC–MS/MS). The chosen target analytes represented different chemical and toxicological NPS classes, such as synthetic cathinones, piperazines, phenethylamines, synthetic cannabinoids, and their metabolites. The procedure involved a rapid sample preparation based on protein precipitation followed by clean‐up utilizing microextraction by packed sorbent (MEPS); the quantitative analysis was performed by UHPLC–MS/MS. The MEPS clean‐up, regardless of non‐quantitative recoveries for some analytes, provided an effective removal of interfering compounds, as demonstrated by reduced matrix effects found at different concentrations for all the analytes. The validation protocol, based on SWGTOX guidelines, demonstrated the suitability of the proposed method for quantitative analysis: linearity range ranged over 3 or 4 orders of magnitude; precision and accuracy tests gave RSD% values below 25%, and accuracy ranged from 85.9% to 107%, accomplishing SWGTOX requirements. Limits of detection (LODs) ranged between 0.005 ng/mL and 0.850 ng/mL and limits of quantification (LOQs) from 0.015 to 2.600 ng/mL. Abstract : A simple, fast, and reliable procedure based on ultra‐high‐performance liquid chromatography–tandem mass spectrometry (UHPLC–MS/ MS) was developed for the simultaneous determination of 31 new psychoactive substances belonging to different chemical classes such as synthetic cathinones, piperazines, phenethylamines, synthetic cannabinoids, and their metabolites in OF samples. The procedure involves a rapid sample preparation method based on a protein precipitation followed by clean‐up based on MEPS. The method has been validated according to the SWGTOX guidelines.